Methane bubbles in the Arctic Ocean. Quantification, variability analysis and modelling of free and dissolved methane from the seafloor to the atmosphere - Jansson, Pär (Limnology and Oceanography: Methods, 2018)
Intensive but heterogeneous and transient seepage of methane (CH4) bubbles from the seafloor exist west of Prins Karls Forland (PKF), offshore western Svalbard. The powerful greenhouse gas CH4, has 32 times higher warming potential than carbon dioxide (CO2) and if seepage of CH4 from the seafloor reaches the atmosphere, it will contribute to the warming climate. Warming of the oceans may in turn, increase the release of CH4 to the water column, resulting in a positive feedback loop. Repeated surveys using an underwater acoustic remote sensing method for the quantification of benthic gas emissions suggest that the seepage west of PKF is modulated by transient opening of gas migration pathways in the sediments. We performed a three-fold repetition of a 64-station oceanographic survey grid with water sampling and simultaneous echosounding. The observations, together with numerical experiments using Lagrangian drifters, showed that that the fate of the emitted methane depends on both the seepage intensity and the temporal dispersion efficiency. We developed a process-based 1-dimensional model resolving free and dissolved gas of several species and several bubble sizes. The model includes user-chosen parametrizations of bubble shapes, rising speeds, and transfer velocities and was designed for easy integration into large-scale ocean circulation models. High-resolution measurements, using a towed, newly developed membrane-inlet laser spectrometer revealed intensive seepage and rapid diffusion near a seepage location 30 km west of Prins Karls Forland, offshore western Svalbard. A new 2-dimensional advection- diffusion model based on hydroacoustically mapped seepage intensity and the vertical distribution predicted by the 1-dimensional model reproduced the observed patterns of dissolved methane along the tow lines in the area. The research brings improved methods for quantification and upscaling of free gas flow rates, and modelling of free and dissolved gases in the water column. We anticipate that they will be used in ...